Heterotopic pregnancy following bilateral tubal ligation: Case report - Kumbak, Banu; Ozkan, Zehra Sema; Simsek, Mehmet (Informa Healthcare, 2011)
Case report A 38-year-old woman presented, one year after bilateral tubal ligation, with vaginal bleeding, vomiting, and stupor. Ten days earlier, she had submitted to a dilatation and curettage for an unexpected intrauterine pregnancy. At the time of this presentation there was rebound tenderness and guarding on abdominal examination, and a 2.5 cm right adnexal mass was detected on transvaginal ultrasound together with free fluid in the pelvis. The serum level of beta-hCG was 8522 mIU/ml. At laparoscopy a right tubal pregnancy and a large haematocele in the pouch of Douglas were detected. A right salpingectomy and a bipolar electrocoagulation of the left tubo-cornual junction were performed laparoscopically. Conclusion Pregnancy after tubal sterilisation may be heterotopic and this possibility should be considered in the differential diagnosis.
Keywords: Heterotopic pregnancy; Tubal ligation; Tubal sterilisation; Laparoscopy